Оцінка критичності вразливостей в операційних системах - Ревізорова, К.; Гріненко, Т. О. (ХНУРЕ, 2019)
Analysis of the vulnerability problem in operating systems. Comparison of existing vulnerability criticality assessment techniques. Review of existing software solutions in the global market. Sample metrics to assess vulnerability criticality.
Keywords: вразливість в операційних системах; оцінка критичності вразливості